CALL-Enhanced L2 Vocabulary Learning: Using Spaced Exposure through CALL to Enhance L2 Vocabulary Retention - Çakmak, Fidel; Namaziandost, Ehsan; Kumar, Tribhuwan (Education research international, 2021)
CALL- and MALL-enhanced learning applications have dominated the field of second language (L2) learning recently. This study aims to investigate the effect of applying a CALL-enhanced L2 vocabulary learning software program on the L2 vocabulary development of English as Foreign Language (EFL) students. 76 preintermediate EFL students registered at a foreign language school were chosen from a total of 156 students after running an Oxford Quick Placement Test (OQPT). The participants were randomly assigned to two groups: the experimental group (EG = 38) and the control group (CG = 38). A vocabulary test as pretest was administered to all the participants before the treatment. During the treatment, the EG learners were requested to utilize a computer-enhanced flashcard software program on their laptops, mobile phones, or other mobile devices at their discretion. By using the program, they could access and utilize a variety of flashcards on many subject matters such as languages, geography, math, and science as well as construct their own flashcards for multiple practices. The CG, on the other hand, was taught through traditional teaching without any CALL tools available. At the termination of the intervention, the vocabulary test was employed as a posttest to both groups to assess the learners’ vocabulary enhancement. The EG outperformed the CG. Findings have led to the reasonable interpretation that L2 vocabulary learning was more productive when the CALL-enhanced flashcard program was utilized for the learning processes.